Adhering interacting cells to two opposing coverslips allows super-resolution imaging of cell-cell interfaces - Julia Sajman (Nature Portfolio, 2021)
Sajman et al. present a simple method to establish cell-cell interfaces for optical microscopy perpendicular to the optical axis. Widely compatible with many imaging techniques, this geometry enables to capture the cell-cell interface in the x/y plane, and allows high-quality diffraction-limited and super-resolution imaging of interfaces between interacting cells.